2012
DOI: 10.1107/s1600536812028097
|View full text |Cite
|
Sign up to set email alerts
|

1-{4-[Bis(4-fluorophenyl)methyl]piperazin-1-yl}ethanone

Abstract: In the title compound, C 19 H 20 F 2 N 2 O, the six-membered piperazine group adopts a slightly distorted chair conformation. The dihedral angle between the mean planes of the two benzene rings is 73.4 (6)°. The mean plane of the ethanone group is twisted from the mean planes of the two benzene rings by 66.7 (8) and 86.2 (6)°. In the crystal, C—H⋯O and C—H⋯F inter­actions link the molecules, forming a three-dimensional … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 9 publications
0
3
0
Order By: Relevance
“…In each of (V) and (VI) the component ions are linked by a combination of O-HÁ Á ÁO and N-HÁ Á ÁO hydrogen bonds to form sheets, which are in turn linked into a three-dimensional assembly by C-HÁ Á Á(arene) hydrogen bonds, as compared to the two dimensional assembly in (II). We also note that structures have been reported for 4-[bis(4-fluorophenyl)methyl)piperazine (VII) (Dayananda et al, 2012a), and for its 1-acetyl derivative (VIII) (Dayananda et al, 2012b), both of which are intermediates on the synthetic pathway to the calcium-channel blocker flunarizine, 1-[bis(4-fluorophenyl)methyl]-4-cinnamyl-piperazine (IX) (Prasanna & Row, 2001). Part of the crystal structure of compound (III) showing the formation of a hydrogen-bonded chain of cations and anions running parallel to the [001] direction.…”
Section: Related Structuresmentioning
confidence: 53%
“…In each of (V) and (VI) the component ions are linked by a combination of O-HÁ Á ÁO and N-HÁ Á ÁO hydrogen bonds to form sheets, which are in turn linked into a three-dimensional assembly by C-HÁ Á Á(arene) hydrogen bonds, as compared to the two dimensional assembly in (II). We also note that structures have been reported for 4-[bis(4-fluorophenyl)methyl)piperazine (VII) (Dayananda et al, 2012a), and for its 1-acetyl derivative (VIII) (Dayananda et al, 2012b), both of which are intermediates on the synthetic pathway to the calcium-channel blocker flunarizine, 1-[bis(4-fluorophenyl)methyl]-4-cinnamyl-piperazine (IX) (Prasanna & Row, 2001). Part of the crystal structure of compound (III) showing the formation of a hydrogen-bonded chain of cations and anions running parallel to the [001] direction.…”
Section: Related Structuresmentioning
confidence: 53%
“…The crystal structures of some related compounds, viz., cis-1-acetyl-4-(4-{[2-(2,4-dichlorophenyl)-2-(1H-1-imidazolyl methyl)-1,3-dioxolan-4-yl]methoxy}phenyl) piperazine: ketoconazole. A crystal structure with disorder (Peeters et al, 1979) (Peeters et al, 2004), 1-{4-[bis (4-fluorophenyl)methyl]piperazin-1-yl}ethanone (Dayananda et al , 2012), cinnarizinium bis(p-toluenesulfonate)dihydrate (Kavitha et al, 2013a) and flunarizinium hydrogen maleate (Kavitha et al, 2013b) have been reported. In view of the importance of the title compound this paper reports its crystal structure.…”
Section: Methodsmentioning
confidence: 99%
“…For the biological activity of piperazine derivatives, see: Bogatcheva et al (2006); Brockunier et al (2004); Elliott (2011); Kharb et al (2012). For the crystal structures of related compounds, see: Dayananda et al (2012); Kavitha et al (2013a,b); Peeters et al (1979Peeters et al ( , 2004. For puckering parameters, see: Cremer & Pople (1975).…”
Section: Related Literaturementioning
confidence: 99%